Potenciais e limitações da indústria de biodiesel no Brasil : um estudo de caso - Zonin, Valdecir José (Universidade do Vale do Rio do Sinos, 2008)
The current energy crisis reflects in the context of societies and points out to a change in this industry under international and national levels. In this context, Brazil comes structuring the National Production and Use of Biodiesel Program (PNPB). This work is based on the case of BSBIOS, gaúcha company inserted under PNPB. The research part of a general analysis of this issue and focus on criteria used to select the raw materials to supply the plants of biodiesel, factors that enable the development of at moment potential and at moment limitations of biodiesel industry. For this, it was developed a reference model that considers: i) short contextualization of the current energy scenario, involving the object of search; ii) structural concepts related matrices productive chosen for this study (soybean, canola, sunflower and castor bean); iii) conceptual aspects related to the production chain, supply chain, logistics and network. Following, the work suggests that the decision on the adoption of agricultur
Keywords: biodiesel; matérias-primas agrícolas; sistemas agroindustriais; bioenergia; agricultural raw materials; biodiesel; systems agroindustriais; bioenergy; Engenharias